2011
DOI: 10.1002/cbic.201000786
|View full text |Cite
|
Sign up to set email alerts
|

Fine Tuning of a Biological Machine: DnaK Gains Improved Chaperone Activity by Altered Allosteric Communication and Substrate Binding

Abstract: DnaK is a member of the Hsp70 family of molecular chaperones. This molecular machine couples the binding and hydrolysis of ATP to binding and release of substrate proteins. The switches that are involved in allosteric communication within this multidomain protein are mostly unknown. Previous insights were largely obtained by mutants, which displayed either wild-type activity or reduced folding assistance of substrate proteins. With a directed evolution approach for improved folding assistance we selected a Dna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…61,63 Indeed, engineering and directed evolution of the activity of other molecular chaperones, including GroEL, Hsp70, ClpX, and Spy, has revealed that minor changes in primary sequence (often a single missense mutation) can suffice to drastically alter substrate specificity or enhance global chaperone activity. [175][176][177][178][179] Indeed, minor alterations in primary sequence in naturally occurring chaperone homologs can also radically change activity. 180 It will be of great interest to engineer and enhance human molecular chaperones to counter specific protein-misfolding events related to neurodegenerative disease.…”
Section: Broader Implications For Engineering Other Chaperones or Dismentioning
confidence: 99%
See 1 more Smart Citation
“…61,63 Indeed, engineering and directed evolution of the activity of other molecular chaperones, including GroEL, Hsp70, ClpX, and Spy, has revealed that minor changes in primary sequence (often a single missense mutation) can suffice to drastically alter substrate specificity or enhance global chaperone activity. [175][176][177][178][179] Indeed, minor alterations in primary sequence in naturally occurring chaperone homologs can also radically change activity. 180 It will be of great interest to engineer and enhance human molecular chaperones to counter specific protein-misfolding events related to neurodegenerative disease.…”
Section: Broader Implications For Engineering Other Chaperones or Dismentioning
confidence: 99%
“…In particular, engineering the human Hsp110, Hsp70, and Hsp40 disaggregase system, 65,[73][74][75][76] to more effectively disaggregate disease substrates is an important goal. Since small changes in primary sequence at specific positions can greatly enhance chaperone activity 61,63,[175][176][177][178][179][180] it appears plausible to isolate therapeutic small molecules that elicit similar enhancements in chaperone activity against disease substrates. 181,182 …”
Section: Broader Implications For Engineering Other Chaperones or Dismentioning
confidence: 99%
“…1B) 2, 3, 1113 to regulate nucleotide binding, hydrolysis and exchange, processes which in turn are coupled to substrate binding and release 2, 3 . Large conformational changes in DnaK accompany the binding and hydrolysis of ATP by DnaK 2, 3, 1420 . The ADP-bound closed conformation promotes stable interactions with substrate, while the ATP-bound open conformation binds weakly to substrates 1420 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the idea that engineering human molecular chaperones, and particularly disaggregases, to enhance their activity against specific protein-misfolding reactions related to neurodegenerative pathologies might not only halt but reverse the progression of these devastating diseases needs further development. Several examples in which the overall activity and substrate specificity of different chaperones have been changed with minor changes in their primary sequence make this proposal reasonable [136,[145][146][147][148].…”
Section: Clpb/hsp104 As Therapeutic Targetsmentioning
confidence: 94%